Managing the unmanageable : how to motivate even the most unruly employee - Loehr, Anne. 4 0 16; Kaye, Jezra; 5 (Pompton Plains, New Jersey : Career Press, 2011)
Presents practical tips for managing difficult employees.
Are unmanageables made or born? -- The 5 Cs -- The excuse-maker -- The grumbler -- The egomaniac -- The loose cannon -- The joker -- The do-gooder -- The wallflower -- The gossip -- The slacker -- The rude-nik -- When it's time to call it quits.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Problem employees.;Employee motivation.;Supervision of employees.;Employees.;Motivation (Psychology);Personnel management; 20; 2